P.60: A Soluble Thermally‐Stable Organic Semiconductor Material for Field‐Effect Transistors. Issue 1 (1st July 2013) - Fukuda, Takashi; Hamura, Satoshi; Watanabe, Makoto
Abstract A novel solution‐processable low molecular weight organic semiconductor material TS‐5, which has high thermal stability and solubility with various aromatic solvents, was developed. Field effect transistors (FET) fabricated using TS‐5 as an active layer, exhibited p‐type transistor responses with mobilities greater than 1.0 cm2/Vs and are stable at 150°C in air condition.